Addition of a blend of exogenous enzymes to broiler chickens diets: impacts on performance and production costs Adição de uma mistura de enzimas exógenas a dietas de frangos de corte: impactos no desempenho e custos de produção - Marchiori M.S.* (2022)
© 2022, Revista Brasileira de Saude e Producao Animal.All Rights Reserved.Broiler diets are based on corn, soybean and wheat production; however, some protein ingredients have many antinutritional factors and low digestibility. The objective of this study was to add a blend of exogenous enzymes to the feed with low nutritional value for broilers to reduce production costs and improve digestibility while maintaining good zootechnical performance. The experimental design was completely randomized, including three treatments with five replications (n=15) each: a) positive control (PC), diet calculated for males with average performance; b) negative control + exogenous enzymes (NC+EE), minimum nutrient diet according to the requirements of the production phase, and the enzymatic blend was added; and c) negative control (NC), minimum levels of nutrients for each phase. At 21 days, the PC group showed greater weight gain and lower feed conversion than the NC (P<0.05). At 42 days, PC had lower feed intake than NC (P=0.040), while lower feed conversion was observed in groups PC and NC+EE than NC (P=0.001). The production efficiency index was higher in the PC treatment, but the NC+EE treatment was higher than the NC (P=0.001). Considering production costs and body weight, we found that NC+EE birds had greater profitability. Therefore, we conclude that the blend of exogenous enzymes added to a diet with minimal nutritional levels has practical application in the broiler production system